The Effect of Ship Crew Governance System on Seafarer’s Employee Engagement under Seaferer’s Employee Agreement at PT. Pelindo Marine Service - Dwireswati, Eka Rahayu; Mudiyanto, Mudiyanto; Wiyono, S. Teguh (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
This study aims to examine the impact of crew governance implementation on the level of employee engagement among crew members employed under Seafarers' Employment Agreements (PKL) at PT Pelindo Marine Service. The governance components analyzed include human resource management systems, payroll and welfare systems, communication, work facilities and environment, as well as job-related factors. A quantitative approach was applied using a survey method, with questionnaires distributed to 106 PKL-status crew members. The collected data were analyzed using simple linear regression to determine the relationship between governance variables and employee engagement levels. The findings reveal that crew governance significantly influences employee engagement. High levels of engagement were reflected in indicators such as work enthusiasm, dedication, and a strong sense of role fulfillment within the company. These results suggest that structured and professional crew management can enhance crew loyalty and their contribution to the achievement of organizational goals.